KEBIJAKAN PENGELOLAAN LINGKUNGAN BERDASARKAN PRINSIP ISLAM UNTUK KEBERLANJUTAN USAHA SEKTOR PARIWISATA - Erwan Iskandar (Journal Of Resource Management, Economics And Business, 2023)
Purpose: The purpose of this research is to examine the impact of Islamic environmental management policies on the sustainability of the tourism sector. Specifically, it aims to investigate how the implementation of these policies influences the environmental practices, reputation, operational efficiency, and overall sustainability of tourism businesses. Research Methodology: This study employs a qualitative research approach, utilizing a combination of literature review and case study analysis. The literature review explores existing literature on Islamic environmental ethics and sustainable tourism development, while the case studies focus on selected tourism destinations where Islamic environmental management policies have been implemented. Data collection methods include document analysis, interviews with key stakeholders, and on-site observations. Results: The analysis reveals that the implementation of Islamic environmental management policies in the tourism sector has positive outcomes. Firstly, it leads to increased awareness and commitment to environmental sustainability among tourism businesses, as reflected in the adoption of eco-friendly practices and the preservation of biodiversity. Secondly, it enhances the reputation and image of tourism businesses, generating positive responses from both the local community and tourists. Lastly, it contributes to operational efficiency by reducing long-term operational costs through resource efficiency and waste reduction practices. Limitations: This research has several limitations. Firstly, the study focuses on a limited number of case studies, which may limit the generalizability of the findings. Secondly, the research relies on self-reported data from tourism businesses, which may introduce bias. Lastly, the study does not examine the economic impacts of Islamic environmental management policies on the tourism sector. Contribution: This research contributes to the existing literature by exploring the impact of Islamic environmental management policies on the sustainability of the tourism sector. It provides insights into the potential of Islamic principles in promoting responsible environmental practices and enhancing the overall sustainability of tourism businesses. The findings of this study can inform policymakers, tourism practitioners, and researchers in developing strategies to integrate Islamic values into environmental management practices in the tourism industry.